2021
DOI: 10.3390/su13148016
|View full text |Cite
|
Sign up to set email alerts
|

Do National Values of Culture and Sustainability Influence Direct Employee PDM Levels and Scope? The Search for a European Answer

Abstract: The dynamic development of the global economy has led to the creation of agile and innovative organizations that need to adapt rapidly to new challenges. For that reason, organizations need to make decisions that help them face uncertain situations and be successful. Research has demonstrated that employee participative decision making (PDM) promotes more innovative, flexible, and sustainable organizations. The present paper examines organizational, cultural, and sustainable factors to discover how these varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 120 publications
(137 reference statements)
1
12
0
Order By: Relevance
“…Some past research has found evidence for gender differences in experienced PDM ( Valverde-Moreno et al, 2019 , 2021a , b ), but other research has found no differences ( Kahnweiler and Thompson, 2000 ; Li and Qian, 2016 ). Some studies have included items related to PDM both at the workplace and organization level, however, these studies do not allow for a comparison of results of experienced PDM at both levels, as the responses were either combined into a single PDM scale ( Kahnweiler and Thompson, 2000 ) or items that measure PDM at the organizational level were given more weight due to their greater contribution to the explained variance (European Working condition Survey; Valverde-Moreno et al, 2019 , 2021a ).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Some past research has found evidence for gender differences in experienced PDM ( Valverde-Moreno et al, 2019 , 2021a , b ), but other research has found no differences ( Kahnweiler and Thompson, 2000 ; Li and Qian, 2016 ). Some studies have included items related to PDM both at the workplace and organization level, however, these studies do not allow for a comparison of results of experienced PDM at both levels, as the responses were either combined into a single PDM scale ( Kahnweiler and Thompson, 2000 ) or items that measure PDM at the organizational level were given more weight due to their greater contribution to the explained variance (European Working condition Survey; Valverde-Moreno et al, 2019 , 2021a ).…”
Section: Introductionmentioning
confidence: 97%
“…Participative decision-making (PDM) refers to “the opportunity for an employee to provide input into the decision-making process related to work matters […] or organizational issues” ( Valverde-Moreno et al, 2021b ). The link between perceived PDM and positive workplace outcomes is well-established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations